Marlé€ne Laruelle: migration and social upheaval as the face of globalization in Central Asia - Malafaia, Thiago Corrêa (Revista Brasileira de Ciência Política, 2018)
This book review makes reference to the book Migration and Social Upheaval as the Face of Globalization in Central Asia, edited by Marlé€ne Laruelle, which focuses on the social and human dimensions of globalization and on how the phenomenon acts as a catalyst to migration in Central Asia. The region, convoluted as it is because of political, social, and economic factors, is highly impacted by the opportunities and constraints brought about by the world’s current interconnectedness.